Disruptive technologies that deliver a circular economy for plastics - Katherine E.S. Locock; Andrew Terhorst; Sarah King; Kymberley R. Scroggie (Next Sustainability)
Plastics are ubiquitous and integral to modern life with global production doubling in the next 20 years. Only minimal amounts, however, are reused or recycled with the common methods of dealing with plastic waste i.e., incineration and landfill, and leaking into the environment (pollution) all resulting in a loss of plastic from the economy. A circular economy for plastics reduces plastic pollution and climate effects and provides social and economic benefits. This article reviews the patent landscape and identifies disruptive technologies that contribute to a circular economy for plastics. Using a collaboration between subject matter experts and ChatGPT, we identified five distinct disruptive technology categories and associated keywords that support a circular economy: bioplastics, chemical recycling, synthetic biology, traceable plastics and waste separation. Using the associated keywords, we categorised patents from 2018 to 2022 into these disruptive technologies to assess current trends. The patent landscape was challenging to navigate due to the deliberately broad language used to construct patents, leading to many irrelevant patents being categorised. Low technology readiness levels of some patents examined also limits the current disruptiveness of these technologies. Adequate financial funding and economic incentives were the most evident barriers to disruptive technology maturity and uptake.